The vulnerability of buildings to a large-scale debris flow and outburst flood hazard cascade that occurred on 30 August 2020 in Ganluo, southwest China - L. Wei; K. Hu; S. Liu; L. Ning; L. Ning; X. Zhang; X. Zhang; Q. Zhang; Q. Zhang; Md. A. Rahim; Md. A. Rahim; Md. A. Rahim (Natural Hazards and Earth System Sciences)
In mountainous areas, damage caused by debris flows is often aggravated by subsequent dam-burst floods within the main river confluence zone. On 30 August 2020, a catastrophic disaster chain occurred at the confluence of the Heixiluo Gully and Niri River in Ganluo County, southwest China, consisting of a debris flow, the formation of a barrier lake, and subsequent dam break that flooded the community. This study presents a comprehensive analysis of the characteristics of the two hazards and the resulting damage to buildings from the cascading hazards. The peak discharge of the debris flow in the gully mouth reached 1871 m3 s−1. Following the dam break, the flood with a peak discharge of 2737 m3 s−1 significantly altered the main river channel, causing a 4-fold increase in flood inundation compared to an ordinary flood. Three hazard zones were established based on the building damage patterns: (I) primary debris flow burial, (II) secondary dam-burst flood inundation, and (III) sequential debris flow burial and dam-burst inundation. Vulnerability curves were developed for Zone (II) and Zone (III) using impact pressures and inundation depths, and a vulnerability assessment chart is presented that contains the three damage categories. This research addresses a gap in the vulnerability assessments of debris flow hazard cascades and can support future disaster mitigation within confluence areas.